2018
DOI: 10.1093/tas/txy138
|View full text |Cite
|
Sign up to set email alerts
|

Survey of cow-calf producer perspectives on management strategies and industry challenges. Part 1: handling practices, and health and industry challenges

Abstract: The objectives of this study were to benchmark cow-calf producer perspectives on management strategies and challenges, and to determine if demographic differences and Beef Quality Assurance (BQA) certification status influenced the frequency of certain management strategies. A total of 1,414 responses from cow-calf producers in 44 states were collected through an online survey conducted in partnership with BEEF, a producer-focused magazine. Survey recipients were asked 30 questions to gather demographic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
10
1
3
Order By: Relevance
“…Beef cattle, equine, poultry, and swine Extension Facebook pages had similar follower demographics; most followers were female, middle-aged, and from the United States. Beef and dairy cattle followers in this study tended to be younger than average ages previously reported for U.S. beef (55 to 70 years) and dairy cattle producers (>50 years; Martin et al, 2018;Sitienei et al, 2020;USDA NASS, 2015Wagner et al, 2020). In contrast, age demographics observed for equine, poultry, and swine followers were consistent with past reports for U.S. equine caretakers (45 to 60 years) and poultry (35 to 64 years) and swine producers (averaged 37 to 51 years; American Horse Council, 2018; Simpson et al, 2020;Stowe, 2012;USDA NASS, 2014, 2020.…”
Section: Discussioncontrasting
confidence: 45%
“…Beef cattle, equine, poultry, and swine Extension Facebook pages had similar follower demographics; most followers were female, middle-aged, and from the United States. Beef and dairy cattle followers in this study tended to be younger than average ages previously reported for U.S. beef (55 to 70 years) and dairy cattle producers (>50 years; Martin et al, 2018;Sitienei et al, 2020;USDA NASS, 2015Wagner et al, 2020). In contrast, age demographics observed for equine, poultry, and swine followers were consistent with past reports for U.S. equine caretakers (45 to 60 years) and poultry (35 to 64 years) and swine producers (averaged 37 to 51 years; American Horse Council, 2018; Simpson et al, 2020;Stowe, 2012;USDA NASS, 2014, 2020.…”
Section: Discussioncontrasting
confidence: 45%
“…Survey demographic information is found in detail in the paired paper, Martin et al (unpublished). Briefly, those who responded to the survey were most frequently aged 55 to 70, with beef cows in the Midwest region of the United States, with a beef cow inventory of 51 to 200 cows ( Martin et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…As referenced in Part I of Martin et al (2019) , survey questions regarding current management and marketing practices on U.S. cow-calf operations were developed by Colorado State University in partnership with Penton Research (Penton, New York, NY). The survey was constructed for electronic dissemination using Qualtrics survey software (Qualtrics, Provo, UT).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most significant diseases in beef cattle is Infectious Bovine Keratoconjunctivitis (IBK), commonly known as pinkeye [ 1 3 ]. IBK costs the US beef cattle industry more than 150 million US dollars annually and a recent survey ranked it as the third highest animal health challenge with 12.5% of producers indicating IBK was the most significant animal health challenge [ 4 ]. The clinical signs of IBK are variable with afflicted animals exhibiting corneal ulceration and edema [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%